Coping strategies for four factors of stress among UiTM Jasin students / Nur Syuhada Muhammat Pazil, Norwaziah Mahmud and Siti Hafawati Jamaluddin - Muhammat Pazil, Nur Syuhada; Mahmud, Norwaziah; Jamaluddin, Siti Hafawati (UiTM Cawangan Perlis, 2021)
University students often face different kinds of stress such as problems with studies, family, friends and financial. This predisposes them to anxiety, sadness, anger and depression. To overcome their stress, students use different types of coping strategies. This study aims to investigate the stress level and the coping strategies by the university students and also to identify the relationship between the effects of stress based on their gender. The data in this study are primary data that were collected through direct questionnaire. Descriptive analysis and chi-square test were used to analyse the data. The result of this study indicates that a majority of the students have moderate level of stress. Many of the students become sad when they are in stress. In order to reduce the stress, most of the students sleep, followed by listening to music. The chi-square test shows no relationship between the effects of stress among female and male students.